Effect of lead oxide on concrete density for radiation shielding purposes - Othman, Siti Amira (2021)
Selection of suitable shielding materials depends on the type, intensity and energy of radiation source, as well as the shielding properties such as mechanical strength, economic preparation and resistance to radiation damage. When compared to ordinary concrete, the addition of some materials with various fractions in the composition of concrete has provided concrete forms more efficient for gamma ray shielding. Concrete has proven to be an tremendous and adaptable shielding material with a well-established linear attenuation coefficient for gamma rays and neutrons. The objectives of this study is to determine the exact composition of concrete constituents and its density. Concrete samples were prepared by mixing cement, water, aggregate and additive with different composition and densities. Density was increases by decreasing the aggregates percent and increasing the additives such as lead oxide. Sample will be compacting to forming a solid material through pelleting and sintering process. Finally, it will undergo for radiation attenuation test. It was found that, substitution of lead oxide by aggregate causes increasing in the specific density and compressive strength of the concrete.